Ameliorative Potentials of Justicia Carnea and Cnidoscolus Aconitifolius on the Fecundity of Chloramphenicol-Induced Lymphoma Rats - Onyegeme-Okerenta Blessing Minaopunyea; Omeje Henry Chimeziea (Journal La Lifesci, 2022)
Justicia carnea and Cnidoscolus aconitifolius were tested for their capacity to ameliorate the fecundity of chloramphenicol-induced lymphoma in rats. Seventy male Wistar rats weighing an average of 128g were randomly divided into 14 groups of five rats each. Group 1 was provided with commercial rat diet and water on a daily basis. For 28 days, rats in groups 2-14 received 250mg/kg bodyweight chloramphenicol by oral intubation. Group 2 received no therapy and is thus referred to as the negative control group. The remaining groups (3–14) received aqueous leaf extracts of J. carnea (ALEJC) (Groups 3-6), C. aconitifolius (ALECA) (Groups 7–10), or a combination of both extracts (Groups 11–14) at dosages of 500mg/kg, 1000mg/kg, 1500mg/kg, and 2000mg/kg, respectively, for 28 days. After anaesthesia with ether, blood was drawn from the retro-orbital venous plexus to determine the activities of oxidative stress indicators such as superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), and glutathione (GSH). The testes were dissected for histological inspection and the semen were collected for analysis. The results indicated a significant (p0.05) increase in weight across groups, as well as a reduction in sperm volume, viability, and motility in group 2 animals as compared to group 1. SOD and GSH levels increased significantly, but MDA levels increased in a non-significant (p>0.05) manner. The results indicated that the extracts had a beneficial impact on infertility associated with excessive chloramphenicol exposure.